The role of non-state providers in informal science, technology, engineering and mathematics (STEM) education: a Malaysian perspective. Issue 1 (2nd January 2023) - Mohamed Anuar, Aizuddin; Chankseliani, Maia
ABSTRACT: The role of non-state providers in the provision of education has been expanding globally. However, there is a dearth of literature on the role of non-state providers in informal education, especially when delivered alongside formal education in schools predominantly under government purview. Using a mixture of methods designed with surveys and interviews involving 32 non-state providers of informal STEM education in Malaysia, this study provides new empirical material to understand the role of non-state providers in informal STEM education. Non-state providers play a complementary role to the government's provision of formal STEM education through the informal variant, motivated by concerns of posterity and national development. At the same time, instances of political competition and bureaucratic barriers are at odds with the government's aspirations for partnership with non-state providers in order to raise students' interest in STEM.